Knowledge and attitude towards pain management. A comparison between oncology and non-oncology nurses in Jordan - Abed El-Rahman, Mona; Al Kalaldeh, Mahmoud Taher; Muhbes, Fakhria (International Journal of Advanced Nursing Studies, 2013)
Background: Knowledge and attitudes of nurses toward pain management have an influence on medical judgment and patients' perception of pain control. Aim: To assess and compare oncology and non-oncology nurses' knowledge and attitudes toward pain management. Method: A cross sectional descriptive comparative design was used. Nurses were recruited conveniently from one specialized oncology center and one main general medical city in Jordan. Participants were required to complete a specific questionnaire. The total number of participant was 207 nurses (124 oncology and 93 non-oncology nurses). Results: It was evident that oncology nurses received post-registration training or courses in the field of pain management more than non-oncology nurses. Both oncology and non-oncology nurses exhibited an appropriate knowledge and attitude toward pharmacological and non-pharmacological pain management strategies. However, oncology nurses scored higher in the overall knowledge and attitude toward pain compared to non-oncology nurses. Nurses showed knowledge deficit in assuming the risk for addiction and the use of narcotics in pediatric patients. Conclusions: The study revealed that oncology nurses were more knowledgeable compared to non-oncology nurses in managing pain. Professional development for nurses in the field of pain management is required whether during academic preparations or post-graduation.